Synthesis of Azo Reactive Dyes Containing Aldehyde Group - SEKAR, N.; S. DEULGAONKAR, DHANANJAY (Asian Journal of Chemistry, 2010)
A new series of reactive dyes containing formyl group were prepared by diazotizing 2-amino-4-chloro-5-formylthiazole and coupling with γ-acid i.e., naphthionic acid. Bisazo dyes based on H-acid were prepared. The dyes were applied on wool, silk and nylon and their fastness properties were measured.